Negotiating Climate Change : The Inside Story of the Rio Convention (Cambridge Cambridge University Press)
Two years of intense and often dramatic negotiations culminated in the signing of a Framework Convention on Climate Change at the Earth Summit in Rio de Janeiro, Brazil. This compelling book reconstructs the dynamics of those negotiations, based on eye-witness accounts. The main contributors, each a principal player in the drama, have been selected to reflect the perspectives of the most important interest groups and institutions involved in the negotiations, including the OECD, oil-importing developing nations, private industry and non-governmental organisations. These individual accounts are integrated into an edited volume that provides a multi-dimensional assessment of the negotiating process, focusing on the competitive and co-operative interactions among nations, regional alliances, international institutions, corporations and non-governmental organisations.
Keywords: Climatic changes